2021
DOI: 10.1177/01945998211026837
|View full text |Cite
|
Sign up to set email alerts
|

Are Multiple Tests Necessary for Salivary Pepsin Detection in the Diagnosis of Laryngopharyngeal Reflux?

Abstract: Objectives To evaluate the necessity of multiple salivary pepsin tests within a day when diagnosing laryngopharyngeal reflux. Study Design Prospective cohort study. Setting Tertiary hospitals. Methods A total of 138 patients with signs and/or symptoms associated with laryngopharyngeal reflux were included. Salivary pepsin was detected on the day of 24-hour pH monitoring, and the results of salivary pepsin detected once in the morning and multiple times in 1 day were compared with the results of pH monitoring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…Two pH monitoring probes are located in the lower esophagus and above the upper esophageal sphincter. We placed the laryngopharyngeal pH monitoring probe in the posterior region of the cricoid cartilage under direct electronic laryngoscopy and wrapped it in mucosa 20 . The LPR diagnosis was based on the occurrence of ≥1 acid or nonacid HRE 6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two pH monitoring probes are located in the lower esophagus and above the upper esophageal sphincter. We placed the laryngopharyngeal pH monitoring probe in the posterior region of the cricoid cartilage under direct electronic laryngoscopy and wrapped it in mucosa 20 . The LPR diagnosis was based on the occurrence of ≥1 acid or nonacid HRE 6 .…”
Section: Methodsmentioning
confidence: 99%
“…It has also been proposed that saliva samples collected for testing after the appearance of significant reflux symptoms have good diagnostic value 16 . However, some studies have indicated that single tests in the morning are too highly missed to be of good diagnostic value, but that testing at multiple time points during the day (12 tests in total) can significantly improve the diagnostic value 17 . However, some patients complain that collecting 12 saliva samples during the day is a burden.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the pepsin saliva measurement is not ready for clinical application for many reasons [ 84 ]. First, the pepsin saliva concentration may significantly vary throughout the testing day [ 85 , 86 , 87 ]. This variation may be attributed to both physiologic and pathologic modifications of esophageal motility and sphincter tonicity, which may be related to lifestyle, meal composition and autonomic nerve dysfunction (anxiety/stress) [ 85 , 86 , 87 , 88 ].…”
Section: Diagnosticmentioning
confidence: 99%
“…First, the pepsin saliva concentration may significantly vary throughout the testing day [ 85 , 86 , 87 ]. This variation may be attributed to both physiologic and pathologic modifications of esophageal motility and sphincter tonicity, which may be related to lifestyle, meal composition and autonomic nerve dysfunction (anxiety/stress) [ 85 , 86 , 87 , 88 ]. Second, the best time of saliva collection, which may be defined as the saliva collection associated with the highest accuracy, sensitivity and positive predictive value pepsin test, remains unknown.…”
Section: Diagnosticmentioning
confidence: 99%
See 1 more Smart Citation